Electrolyte and acid-base imbalances and kidney function in children with acute diarrhea: A study from Dr. Soetomo General Academic Hospital 2021–2023 - Arshq Mirza Hamzah; Alpha Fardah Athiyyah; Ulfa Kholili; Sulistiwati Sulistiawati (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Diarrhea is the third leading cause of death in children under five, causing nutritional deficits that hinder growth, cognitive, and academic performance. Each episode before the age of 2 years increases the risk of stunting by 5%. Systematic data, such as sociodemographic, clinical characteristics, and laboratory characteristics, are important for prevention. This descriptive observational study used a retrospective design based on medical records of children with acute diarrhea treated at Dr. Soetomo General Hospital, Surabaya, from 2021 to 2023. A total of 461 subjects met the criteria; 429 underwent electrolyte imbalance testing, 198 were assessed for urea and creatinine levels, and 68 had their acid-base balance evaluated. A total of 288 subjects (62.5%) were male children; 262 patients (75%) were 0-12 months old; 253 (61%) had good nutritional status; 339 (73.5%) underwent therapy for less than 1 week; and 402 patients (65%) recovered. A total of 40% experienced mild-moderate and severe dehydration with neurologic (16.4%) and respiration comorbidities (16.2%). Electrolyte disturbances included hyponatremia (33.1%), hypokalemia (12.1%), hyperchloremia (50.2%), increased urea (28.3%), abnormal creatinine (35.4%), hypobicarbonate (75%), and acidosis (63.2%). Therefore, early detection and appropriate management are essential to mitigate further complications and improve recovery outcomes.